Penerapan Metode Moora Pada Sistem Pendukung Keputusan Pemilihan Leader SPG - Br. Gm, Merry Oktaviani (Forum Kerjasama Pendidikan Tinggi (FKPT), 2024)
To improve the performance of companies engaged in services or manufacturing where companies can compete well at regional, national and even international levels by having competitive human resources (HR). Competitive HR employees who can work productively and professionally to achieve the vision, mission and goals of the company. The quality of SPG leader selection is recorded in the employee performance track record, the results of the track record are in the form of SPG leader selection results that have an important role for the company in making decisions in improving the company's HR including identifying the needs of educational development, training, recruitment, selection, promotion, mutation, demotion, leader, reward and punishment. The solution to the above problems is to use a Decision Support System to help determine the selection of SPG leaders, the method used to support solving the above problems is the Multi-Objective Optimization on the basis of Ratio Analysis (MOORA) method, namely by giving weight to each existing alternative. Decision Support System is an interactive system, helping decision making through the use of data and decision models to solve problems that are semi-structured or unstructured. In solving the above problem, you can use Visual Basic programming to determine the weight value of all the SPG leader selection criteria.